Mechanical Properties and Microstructure Damage of Limestone Concrete Under Triaxial Stress - Kaide Liu; Songxin Zhao; Dingbo Wang; Wenping Yue; Chaowei Sun; Yu Xia; Qiyu Wang (Buildings)
This study takes limestone crushed stone concrete as the research object and systematically investigates its mechanical property changes and microstructural damage characteristics under different confining pressures using triaxial compression tests, scanning electron microscope (SEM) tests, and digital image processing techniques. The results show that, in terms of macro-mechanical properties, as the confining pressure increases, the peak strength increases by 192.66%, the axial peak strain increases by 143.66%, the elastic modulus increases by 133.98%, and the ductility coefficient increases by 54.61%. In terms of microstructure, the porosity decreases by 64.35%, the maximum pore diameter decreases by 75.69%, the fractal dimension decreases by 19.56%, and the interfacial transition zone cracks gradually extend into the aggregate interior. The optimization of the microstructure makes the concrete more compact, reduces stress concentration, and thereby enhances the macro-mechanical properties. Additionally, the failure characteristics of the specimens shift from diagonal shear failure to compressive flow failure. According to the Mohr–Coulomb strength criterion, the calculated cohesion is 6.96 MPa, the internal friction angle is 38.89°, and the breakage angle is 25.53°. A regression analysis established a quantitative relationship between microstructural characteristics and macro-mechanical properties, revealing the significant impact of microstructural characteristics on macro-mechanical properties. Under low confining pressure, early volumetric expansion and rapid volumetric strain occur, with microcracks mainly concentrated at the aggregate interface that are relatively wide. Under high confining pressure, volumetric expansion is delayed, volumetric strain increases slowly, and microcracks extend into the interior of the aggregate, becoming finer and more dispersed.